Knowledge of Case Workers and Correctional Officers towards HIV and HCV Infections: Opportunity for Public Health Education in the Correctional System - Pérez, Cynthia M.; Santos, María del Carmen; Torres, Aurinés; Grana, Carlos; Albizu-García, Carmen (Puerto Rico Health Sciences Journal, 2015)
Objective: Given the heavy burden of hepatitis C virus (HCV) and human immunodeficiency virus (HIV) infections in correctional facilities, we examined knowledge about these infections among case workers and correctional officers in penal institutions in Puerto Rico. Methods: We used data from a cross-sectional study of state prisons, commissioned by the Puerto Rico Department of Correction and Rehabilitation, to assess knowledge about HCV and HIV (10 items each) among 256 case workers and correctional officers from 18 penal institutions selected in the prison system. Total scores for each scale ranged from 0 to 10 points, with higher scores reflecting more knowledge. Results: Of 256 participants, 64.8% were males, 39.6% were aged 30-39 years, and 70.3% were case workers. The percentage of correct responses for knowledge items ranged from 8.5% to 97.0% for HCV infection and from 38.7% to 99.6% for HIV infection. The vast majority (>96%) of participants knew that injection drug users should be tested for HCV infection and that sharing of needle injection equipment and multiple sex partners increase the risk of HIV infection. However, misconceptions about routes of transmission for these viral infections were found, with larger gaps in knowledge for HCV infection. Mean knowledge scores for HCV and HIV infections were 4.20±0.17 and 6.95±0.22, respectively, being significantly (p<0.05) higher for case workers. Conclusion: The findings about HCV and HIV knowledge in an important segment of the correctional system staff support the urgent need for increasing educational opportunities for correctional staff.